CGS quality scalability for HEVC - Shi, Zhongbo; Sun, Xiaoyan; Xu, Jizheng (IEEE International Workshop on Multimedia Signal Processing (MMSP 2011), 2011)
Scalable video coding provides an efficient way to serve video contents at different quality levels. Based on the development of emerging High Efficiency Video Coding (HEVC), we propose two coarse granular scalable (CGS) video coding schemes here. In scheme A, we present a multi-loop solution in which the fully reconstructed base pictures are utilized in the enhancement layer prediction. By inserting the reconstructed base picture (BP) into the list of reference pictures of the collocated enhancement layer frame, we enable the coarse granular quality scalability of HEVC with very limited changes. On the other hand, scheme B supports single loop decoding. It contains three inter-layer predictions similar to the scalable extension of H.264/AVC. Compared to scheme A, it decreases the decoding complexity by avoiding the motion compensation, deblocking filtering (DF) and adaptive loop filtering (ALF) in the base layer. The effectiveness of our proposed two coding schemes is evaluated by comparing with single-layer coding and simulcast.